ความรู้ทางสรวิทยาของครูภาษาอังกฤษและกิจกรรมในชั้นเรียนเพื่อเพิ่มความตระหนักรู้ด้านระบบเสียง และการสอนโฟนิกส์ให้กับนักเรียนชั้นประถมศึกษาตอนต้นโรงเรียนนานาชาติอาร์ซี - ซี, เซียว เว่ย; โหมดหิรัญ, ปราณภา (An Online Journal of Education, 2018)
The present study aimed to 1) assess knowledge of phonology of the early primary International School English teachers; and 2) explore the classroom practices in raising phonological awareness and teaching phonics to their students. Participants were 21 English teachers who were teaching English from grade 1 to grade 3 in an International School. The research instruments included a test of teachers’ knowledge of phonology and a questionnaire of teachers’ classroom practices in raising students’ phonological awareness and teaching phonics. The findings of the study indicated a satisfied level of the English teachers’ phonological knowledge. For the classroom practices, the results revealed different types of classroom practices in raising students’ phonological awareness and teaching phonics. The classroom practices the teachers most frequently implemented were the phoneme manipulation for raising the students’ phonological awareness; and the classroom practices in teaching phonics, the practices of introducing the fundamental blending letter-sound as blending sounds into recognizable letters of words were reported as the most frequently conducted.